RESERVES OF IMPROVEMENT OF RAILS QUALITY. IMPROVING THE TECHNOLOGY OF MICROALLOYING THE RAIL STEEL - Titova, T. M. (Science and Transport Progress, 2005)
Ways of perfection of the technological circuit of producing of rails are considered. It is shown, that microalloying is the important reserve of improvement of quality of rail steel.